Effect of counseling by paraprofessionals on depression, anxiety, somatization, and functioning in Indonesian torture survivors - Larson-Stoa, Deborah; Jacobs, Gerard A.; Jonathan, Abraham; Poudyal, Bhava (Torture Journal, 2018)
The Indonesian population has faced political violence, victimization, and torture throughout the last 70 years. Due to the scarcity of mental health professionals in many low and middle-income countries, counseling programs are increasingly utilizing paraprofessionals to provide support to the affected population as a strategy of task shifting. In this article, we would like to examine the effectiveness of counseling services provided by such trained paraprofessionals. This study was part of program evaluation to determine whether the participants (torture survivors) improved after counseling services provided by trained paraprofessionals in Indonesia. Local communities were invited to join the psychosocial program created and implemented by an NGO in 2005. The 178 participants were recruited from Jakarta, Papua, and Aceh, Indonesia for the program, which aimed to help survivors of violence suffering from “heavy hearts.” The intervention lasted three months, and the follow-up intake was conducted after four months. The results indicated the participants’ anxiety symptoms, depressive symptoms, somatic symptoms, and functioning improved from the intake to the follow-up. The program appeared to have been effective in reducing the participants’ symptoms and impairment in functioning. This indicates that in countries where there is a scarcity of mental health professionals, working with paraprofessionals has the potential to help survivors of torture and violence.